ANALISIS KEBUTUHAN MODAL KERJA PADA CV. BINTANG TIMUR JAYA DI MAKASSAR - Sitti Murniati (AkMen JURNAL ILMIAH, 2016)
The aim of this research was to determine the level of working capital at CV. Bintang Timur Jaya Makassar. The analytical method used in this research is quantitative descriptive analysis. The results of analysis show that working capital requirements which must be owned by the CV. Bintang Timur Jaya in Makassar for 2015 amounted to USD 64,043,539.00. Working capital available in the company (current assets listed on the balance sheet as of December 31, 2014) is Rp 114,148,641.00. CV. Bintang Timur Jaya in Makassar for 2015 had excess working capital of Rp 114,148,641.00. This shows that the working capital provided more than enough in the amount of USD 50,105,102.00 which means that a sufficient working capital or allow the company to operate economically and is not experiencing financial difficulties, for example, to cover the losses and able to cope crisis or emergency without jeopardizing the company's financial condition.